Knowledge, attitude, and practice of patients with major depressive disorder on exercise therapy - Junxiang Cheng; Yaoqing Feng; Zhifen Liu; Dandan Zheng; Hong Han; Na Liu; Shasha Liu; Juan Zhao; Xiaole Li; Shifan Han (BMC, 2024)
Abstract Background This study aimed to explore the knowledge, attitude, and practice (KAP) toward exercise therapy of patients with major depressive disorder (MDD). Methods This cross-sectional study was conducted at the First Hospital of Shanxi Medical University between April and October 2023 in patients with MDD. A self-designed questionnaire was used to evaluate the KAP (Cronbach's α = 0.787). The minimum-maximum scores were 2-23 for knowledge, 11-55 for attitude, and 7-35 for practice. Results A total of 494 valid questionnaires were analyzed. The mean KAP dimension scores were 15.39 ± 3.34/23 (66.91%), 36.54 ± 19.33/55 (66.44%), and 19.33 ± 5.22/35 (55.23%), indicating poor knowledge, negative attitude, and weak practice. Multivariable logistic regression analysis showed that female (OR = 0.613, 95%CI: 0.376-1.000, P = 0.050), urban residence (OR = 0.443, 95%CI: 0.259-0.758, P = 0.003), suburban residence (OR = 0.047, 95%CI: 0.016-0.138, P < 0.001), higher income (OR = 3.889-7.928, all P < 0.001), and unclear self-reported depression level (OR = 0.078, 95%CI: 0.027-0.221, P < 0.001) were independently associated with the knowledge scores. Knowledge scores (OR = 1.102, 95%CI: 1.022-1.188, P = 0.011), female gender (OR = 0.437, 95%CI: 0.246-0.776, P = 0.005), city (OR = 0.410, 95%CI: 0.226-0.744, P = 0.003), married (OR = 3.577, 95%CI: 1.751-7.650, P < 0.001), higher income (OR = 0.065-0.392, both P < 0.050), depressive trend (OR = 2.640, 95%CI: 1.110-6.278, P = 0.028), high depression score level (OR = 0.176, 95%CI: 0.104-0.300, P < 0.001), and unclear self-reported depression score (OR = 0.023, 95%CI: 0.007-0.076, P < 0.001) were independently associated with the attitude scores. Finally, knowledge scores (OR = 1.130, 95%CI: 1.051-1.215, P = 0.001), attitude scores (OR = 1.199, 95%CI: 1.124-1.280, P < 0.001), and city (OR = 0.583, 95%CI: 0.352-0.965, P = 0.036) were independently associated with the practice scores. The structural equation modeling analysis showed that knowledge, but not attitude (β = 0.103, P = 0.092) or practice (β = 0.034, P = 0.603), influenced the depression level (β=-0.074, P < 0.001); attitude influenced practice (β = 0.369, P < 0.001). Conclusion The KAP toward exercise among MDD patients is poor in Shanxi. Females, people living in urban or suburban areas, with lower income, and self-reported unclear depression levels should be targeted by education interventions.